Soviet and Ukrainian Studies of American Philosophy: Translation of Philosophical Texts - Yaroslav Sobolievskyi (International Society of Philosophy and Cosmology, 2018)
Studies of the history of American philosophy by Soviet and Ukrainian philosophers are described in this article. The specifics of the history of philosophy in the Soviet Union under the conditions of official ideology are emphasized; the tradition of translating Western philosophical texts and the appearance of the Russian philosophical lexicon (the language of the Soviet Union) is described. Studies of translation activities and critical literature of Soviet philosophers on American philosophy allow us to study the ideological components that Ukrainian philosophers seek to avoid. The article briefly describes the history of translation activity and some aspects of translations of English texts. The features of the Soviet selection of texts that would be consistent with official ideology are revealed. Also, in the article the most popular and well-known texts of the Soviet period and independent Ukrainians, philosophers and translators (such as, Alexey Bogomolov, Anyur Karimsky, Yuri Melville, Nikita Pokrovsky and others) who worked on American studies are described. The article also mentions two volumes of "American Enlighteners: Selected Works" compiled by Goldberg N. with an introductory article by Bernard Bykhovsky in the multivolume edition of the "Philosophical Heritage". Their contribution to the development of American studies was demonstrated on the basis of an analysis of scientific works: critical literature and translations of primary sources. The article is focused on the need for the absence of a "correct" philosophy, which is a recurrence of the totalitarian practices of Soviet philosophy and ideology.